ANALISIS FAKTOR PENENTU KEUNGGULAN BERSAING PADA LAYANAN JASA KURIR (Studi Pada J&T Express Kabupaten Kendal) - Fauziah, Annisa Fitri; Santoso, Rahmat Budi (Jurnal Publikasi Manajemen Informatika, 2025)
This study aims to identify the determining factors of Competitive Advantage in J&T Express Courier Services in Kendal Regency, Central Java. The research sample consists of 400 respondents from 20 districts in Kendal Regency. The analysis technique used in this study is multiple linear regression analysis. The results of this study show that Marketing Mix, Service Quality, and Brand Trust are key factors determining Competitive Advantage in the case of J&T Express Courier Services in Kendal Regency. This study also highlights that there are other factors, aside from the variables examined, which may influence the Competitive Advantage of the Courier Service.